Menulis Berita Dan Feature Keislaman - Erwan Efendi; Khairul Imam Damanik; Tri Purnama Sari (Jurnal Pendidikan dan Konseling (JPDK), 2023)
Online media reporting often causes boredom for readers, such as hard news types. One type of news, namely features, is news that fights the stalemate of news structures in general as a complement by prioritizing creativity which involves the imagination of the writer and has aesthetic value in it and can influence the feelings of the reader such as emotion, joy. The human value in the feature gives more interest to readers because human life is interesting to make stories from various sides. The Feature rubric on the Islamic news portal Hidayatullah.com is a special rubric that provides feature works for readers, the purpose of this research is to find out the application of feature human discourse analysis theory to the Islamic news portal Hidayatullah.com Feature rubric. This research method uses a qualitative approach with the method of discourse analysis. The results of this study use the theory of discourse analysis, consisting of three structures, namely the macro structure, super structure and micro structure. The macro structure is used to analyze themes or related to thematic. The superstructure is related to the schematic where the author explains the cohesiveness and structure between paragraphs at the opening, content, and closing. For micro-structures related to syntactic semantics, stylistics is described in a complete and clear manner, the lexicon uses terms that are easy to understand, rhetoric and metaphors are used as message markers to the reader.